Effect of Nitrogen Fertilizer on Growth, Yield and Sucrose Concentrationof Sugar Beet (Beta vulgaris L.) Under Saline Soil in El Kadaro, Sudan - Sulfab, Hatim A.; Idris Bakhit, Baha Eldin M.; Hagalla, Elshiekh; A., Karima; I, Asha; Marajan, Wael A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Field experiments were conducted on two consecutive seasons (2014/2015 and2015/2016) at the Agricultural Farm of Bahri University in Elkadaro (Sudan), where is the soil classified as slightly saline at surface and saline sodic at subsurface soil. Seed of sugar beet Ballede variety was obtained from the Agricultural Research Station in Wad Madani.The objectives of the experiments were studied the effect of mineral nitrogen fertilizer on growth, root yield and juice quality of sugar beet under saline soil. The nitrogen fertilizer was applied as urea at the rate of 0Kg N/ha, 40Kg N/ha, 60 Kg N/ha, and 80 Kg N/ha.The experiments were laid out in randomized complete block design with four replicates. The results showed that 80 Kg N/ha treatment was highly significant (P< 0.01) increased leaves number, leaf area index, leaves fresh weight, shoot fresh weight, root fresh weight and root diameter per plant over all other treatments and the control. However treatment 60KgN/ha significantly (P< 0.05) produced more leaves number, shoot fresh weight, root fresh weight and root diameter per plant. Each of nitrogen treatments significantly (P< 0.05) increased root yield per plant over the control. The increases in root yield compared to control were 13% 33% and 46% for the 40 Kg N/ha, 60 Kg N/ha, and 80 Kg N/ha respectively. Each level of nitrogen fertilizer significantly (P< 0.05) reduced Sugar percentage, (Pol %), Brix percentage, and Purity percentage. However, treatments 60KgN/ha and 80KgN/ha significantly (P<0.05) increased moisture percentage over the other treatments